Le fantastique (de l’extrême) contemporain en France : conceptions, enjeux, perspectives - Gadomska, Katarzyna (Romanica Silesiana, 2024)
The aim of this article is to show the evolution of contemporary fantastic literature in France. The article describes the reform of the genre carried out by the writers of the so-called first wave (like Alain Dorémieux, Jean-Pierre Andrevon) in the 1980s. Among their theoretical postulates, the following should be mentioned: rejection of traditional fantastic literature, banality of horror taking place in everyday life, transfers between popular genres, intermedia transfers, inspiration of contemporary philosophy and deep ecology. The article also shows the later stages of the reform continued by the second generation of fantastiqueurs (Pascal Malosse, Rémi Karnauch). Their fiction is determined by the absurd, the grotesque, and the surreal. The boundaries between the fantastic and mainstream are blurry as well.